1995
DOI: 10.1016/0742-051x(94)00013-v
|View full text |Cite
|
Sign up to set email alerts
|

Using the case method in teacher education: The role of discussion and experience in teachers' thinking about cases

Abstract: , B.B. (1995). Using the case method in teacher education: The role of discussion and experience in teachers' thinking about cases. Teaching and Teacher Education, 11, 63-79. Made available courtesy of Elsevier: http://www.elsevier.com ***Reprinted with permission. No further reproduction is authorized without written permission from Elsevier. This version of the document is not the version of record. Figures and/or pictures may be missing from this format of the document.***

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
2
13

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 13 publications
6
97
2
13
Order By: Relevance
“…Our finding concerning case-based teaching is similar to that of Levin (1995), who indicates that the social interaction during the discussion of a case appears to be the source of changes in teachers' thinking. She concludes that '… the conflicting ideas served as a catalyst for important changes in teachers' thinking' (Levin 1995:75).…”
Section: Appropriate Use Of Social Skillssupporting
confidence: 85%
“…Our finding concerning case-based teaching is similar to that of Levin (1995), who indicates that the social interaction during the discussion of a case appears to be the source of changes in teachers' thinking. She concludes that '… the conflicting ideas served as a catalyst for important changes in teachers' thinking' (Levin 1995:75).…”
Section: Appropriate Use Of Social Skillssupporting
confidence: 85%
“…Practitioners learn when they have ongoing opportunities to engage with the full range of challenging problems associated with their practice and receive authentic feedback (Ericsson 2006). Discussion of dilemma situations can help program leaders obtain this deliberate practice; it can help them become more aware of underlying nuances, assumptions, values, principles, and options in different situations (Banks 2005;Levin 1994). In education, business, and medical fields, challenging case studies are often used to help trainees understand the realworld complexities of practice.…”
Section: Implications For Practice Practitioner Training and Managementioning
confidence: 99%
“…In education, business, and medical fields, challenging case studies are often used to help trainees understand the realworld complexities of practice. Preliminary evidence indicates that they help sharpen people's critical thinking skills, apply concepts and precedents, and feel more comfortable making decisions (Harrington 1995;Levin 1994). …”
Section: Implications For Practice Practitioner Training and Managementioning
confidence: 99%
“…Researchers have observed that when instructors decrease the process of closure, students acquire less knowledge from the learning process (Gertzman & Kolodner, 1996;Hmelo, Holton, & Kolodner, 2000). Levin (1995) also noted that discussion appeared to act as an important catalyst for reflection for experienced teachers, helping them to learn through the writing or reading that was prompted through the reflection process. Collins and Brown (1988) highlighted the importance of reflection during reasoning activities.…”
Section: After Discussionmentioning
confidence: 99%
“…As a problem-centered approach to teaching, CBL relies on class discussion as its primary strategy (Dabbagh, Jonassen, Yueh, & Sanouilous, 2000;Heckman & Annabi, 2006;Levin, 1995). As described by Andersen and Schiano (2014), "The core of case teaching-and most of the art of it clies in managing the students' discussion" (p. 66).…”
Section: Introductionmentioning
confidence: 99%